Mycobacterium tuberculosis subverts negative regulatory pathways in human macrophages to drive immunopathology. - Patience T Brace; Liku B Tezera; Magdalena K Bielecka; Toby Mellows; Diana Garay; Shuye Tian; Lucinda Rand; Justin Green; Sanjay Jogai; Andrew J Steele; Timothy M Millar; Tilman Sanchez-Elsner; et al. (PLoS Pathogens)
Tuberculosis remains a global pandemic and drives lung matrix destruction to transmit. Whilst pathways driving inflammatory responses in macrophages have been relatively well described, negative regulatory pathways are less well defined. We hypothesised that Mycobacterium tuberculosis (Mtb) specifically targets negative regulatory pathways to augment immunopathology. Inhibition of signalling through the PI3K/AKT/mTORC1 pathway increased matrix metalloproteinase-1 (MMP-1) gene expression and secretion, a collagenase central to TB pathogenesis, and multiple pro-inflammatory cytokines. In patients with confirmed pulmonary TB, PI3Kδ expression was absent within granulomas. Furthermore, Mtb infection suppressed PI3Kδ gene expression in macrophages. Interestingly, inhibition of the MNK pathway, downstream of pro-inflammatory p38 and ERK MAPKs, also increased MMP-1 secretion, whilst suppressing secretion of TH1 cytokines. Cross-talk between the PI3K and MNK pathways was demonstrated at the level of eIF4E phosphorylation. Mtb globally suppressed the MMP-inhibitory pathways in macrophages, reducing levels of mRNAs encoding PI3Kδ, mTORC-1 and MNK-1 via upregulation of miRNAs. Therefore, Mtb disrupts negative regulatory pathways at multiple levels in macrophages to drive a tissue-destructive phenotype that facilitates transmission.